2019
DOI: 10.3389/fpls.2019.01170
|View full text |Cite
|
Sign up to set email alerts
|

Together But Different: The Subgenomes of the Bimodal Eleutherine Karyotypes Are Differentially Organized

Abstract: Bimodal karyotypes are characterized by the presence of two sets of chromosomes of contrasting size. Eleutherine bulbosa (2n = 12) presents a bimodal karyotype with a large chromosome pair, which has a pericentric inversion in permanent heterozygosity with suppressed recombination, and five pairs of three to four times smaller chromosomes. Aiming to understand whether high copy number sequence composition differs between both chromosome sets, we investigated the repetitive DNA fraction of E. bulbosa and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…The application of these antibodies in a wide range of species is possible due to the evolutionarily conserved amino acid sequence of histone H3. However, in some monocentric species, the application of anti-H2AT120ph resulted in additional non-pericentromeric signals (Baez et al 2019 ; Sousa et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of these antibodies in a wide range of species is possible due to the evolutionarily conserved amino acid sequence of histone H3. However, in some monocentric species, the application of anti-H2AT120ph resulted in additional non-pericentromeric signals (Baez et al 2019 ; Sousa et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the recombination rate tends to differ between the chromosome sets of a bimodal karyotype over time [ 22 , 68 ]. This characteristic is necessary to maintain the asymmetry of a bimodal karyotype after its formation [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fusion/fission events can originate bimodal karyotypes, which are characterized by the existence of classes of chromosomes with divergent sizes [ 20 ]. The origin of the bimodal karyotype can be related to fusion/fission-type chromosomal rearrangements, the hybridization process with subsequent polyploidy [ 21 ] or differential accumulation of repetitive sequences in certain chromosomes [ 22 ]. In bimodal karyotypes of some monocotyledonous plants and vertebrate animals, microchromosomes were recorded, which are extremely small in size, similar to dots, whose morphology is not possible to determine [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of these antibodies in a wide range of species is possible due to the evolutionarily conserved amino acid sequence of histone H3. However, in some monocentric species, the application of anti-H2AT120ph resulted in additional non-pericentromeric signals (Baez et al, 2019;Sousa et al, 2016).…”
Section: How To Identify Holocentricity?mentioning
confidence: 99%